Addison's disease - Soumya Brata Sarkar; Subrata Sarkar; Supratim Ghosh; Subhankar Bandyopadhyay (Wolters Kluwer Medknow Publications, 2012)
Addison's disease is a rare endocrinal disorder, with several oral and systemic manifestations. A variety of pathological processes may cause Addison's disease. Classically, hyperpigmentation is associated with the disease, and intraoral pigmentation is perceived as the initial sign and develops earlier than the dermatological pigmentation. The symptoms of the disease usually progress slowly and an event of illness or accident can make the condition worse and may lead to a life-threatening crisis. In this case, several oral as well as systemic manifestation of the Addison's disease was encountered.